1982
DOI: 10.1002/jhrc.1240050109
|View full text |Cite
|
Sign up to set email alerts
|

Splitless headspace gas chromatography with capillary column using automatic electropneumatic injection

Abstract: Splitless sample injection plays an important role in kinetic studies and sometimes also in trace analysis since this technique enables one to avoid the withdrawal of large amounts of substances from the sample, a quantity perhaps 10-50 times more than that needed for the investigation.Perkin Elmer instruments (F 42, F 45, H S 6) are widely used with capillary columns and splitting for headspace analysis. The electropneumatic dosing system of these instruments [5] works in such a way that the amount of samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The calibration shown in figure has an S-shape. Having increased the signal-to-noise ratio 5-fold (the method used was described by Leisztner et al [10]), we obtained a linea relationship as demonstrated in figure 2. The signal-to.…”
Section: Possibilities Of Correct Measurement Controlmentioning
confidence: 94%
“…The calibration shown in figure has an S-shape. Having increased the signal-to-noise ratio 5-fold (the method used was described by Leisztner et al [10]), we obtained a linea relationship as demonstrated in figure 2. The signal-to.…”
Section: Possibilities Of Correct Measurement Controlmentioning
confidence: 94%